Stunting: Issues And Prevention Efforts by Stakeholders - Faizah Luthfia; T Titania; Moh Taufik Hidayat; Raden Mahendra Haryo Bharoto (CV. Media Digital Publikasi Indonesia, 2025)
This study aims to analyze the implementation of policies and the role of stakeholders in addressing stunting reduction in Cicurug Village. The issuance of Majalengka Regent's Decision No. KS.02.00.00/KEP.294-DP3AKB/2022 regarding the Stunting Reduction Acceleration Team marks the initial step for stakeholders to collaborate in reducing stunting rates. The issue of stunting must be re-examined, as the stunting rate in Majalengka District increased from 1.26% to 2.17% in 2024. This study employs Van Meter and Van Horn's theory, which identifies six indicators of successful policy implementation: policy standards and objectives, resources, communication, characteristics of implementing agencies, socio-economic and political environment, and attitudes of implementers. The research methods used are qualitative and descriptive. Data collection techniques include interviews, observations, and documentation. The research findings on the implementation of stunting policies by stakeholders revealed several major issues in the implementation of the stunting reduction program, including insufficient coordination among local government agencies, a shortage of specialized personnel at the community health center level, and low public awareness of the importance of participating in posyandu activities. The research results are expected to provide an overview that the implementation of stunting policies by stakeholders in Majalengka District has not yet been fully optimized.